Minor psychic disorders in nursing workers at a psychiatric hospital - Oliveira,Elias Barbosa de (2020)
Abstract Objective: To describe the frequency of suspicion of minor psychic disorders and their symptoms in nursing workers at a psychiatric hospital. Method: Cross-sectional study carried out in 2018 with nursing workers at a psychiatric hospital in the city of Rio de Janeiro, Brazil. Data were collected by using an instrument with sociodemographic, work, and health variables. The Self-Reporting Questionnaire-20 was used to verify minor psychic disorders. Results: Ninety workers participated in the study. The frequency of minor psychic disorders in the sample was equal to 32.2%. The questions that showed the highest frequencies of affirmative answers were: “Do you feel nervous, tense, or worried?” (51.1%), “Dou you often have headaches?” (41.1%), “Is your daily working suffering?” (37.8%), “Do you have uncomfortable feelings in your stomach?” (36.7%), “Do you find it difficult to enjoy your daily activities?” (27.8%), and “Are you unable to play a useful part in life?” (22.2%). Conclusion: The predominance of symptoms of reduced vital energy and somatization suggest stress and risk of mental disorders.